2012
DOI: 10.1177/0897190012451911
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pharmacist Utilization of a Poison Center as a Resource for Patient Care

Abstract: The objective of this study was to evaluate pharmacist use of a Regional Poison Information Center (RPIC), identify potential barriers to utilization, and provide strategies to overcome these barriers. All calls placed to a RPIC by a pharmacist, physician, or nurse over a 5-year period were retrieved. These data were analyzed to assess the pharmacist utilization of the RPIC and the variation of call types. Additionally, a survey, designed to assess the past and future use of the RPIC by pharmacists, was distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…13 Usually, agents working in medical call centers mainly consist of physicians, psychiatrists, pharmacists, or nurses. 14 In general, the satisfaction rates among agents working in call centers were not very high and could depend on several factors that may include the job nature, workload, work management, type of customers, and even the marital and educational status of the workers. 15 In Europe, two previous studies showed that the mean satisfaction percentage of agents working in the call center was not more than 66%, which indicates moderate satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…13 Usually, agents working in medical call centers mainly consist of physicians, psychiatrists, pharmacists, or nurses. 14 In general, the satisfaction rates among agents working in call centers were not very high and could depend on several factors that may include the job nature, workload, work management, type of customers, and even the marital and educational status of the workers. 15 In Europe, two previous studies showed that the mean satisfaction percentage of agents working in the call center was not more than 66%, which indicates moderate satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Medical call centers provide medical information and assistant to people to decrease hospital visits and to help in dealing with patients' various existing illnesses [22]. Usually, agents working in medical call centers mainly consist of physicians, psychiatrists, pharmacists, or nurses [23].…”
Section: Discussionmentioning
confidence: 99%